Size controlled fabrication of cellulose nanoparticles for drug delivery applications - Chin, Suk Fun; Fiona Beragai, Jimmy; Pang, Suh Cem (Editions de Sante, 2018)
Spherically shaped cellulose nanoparticles with average particle diameter range between 70 and 365 nm were fabricated from cotton fibers by a simple nanoprecipitation method. The average particle diameter of cellulose nanoparticles could be precisely controlled by modulating the synthesis conditions such as cellulose solution concentration and volume ratio of solvent/non-solvent. Methylene blue (MB) as a model hydrophilic drug was loaded onto cellulose nanoparticles via the in-situ nanoprecipitation process. The loading efficiency and release profile of MB were observed to be affected by the average particle diameter of cellulose nanoparticles. © 2017